2000
DOI: 10.4049/jimmunol.164.7.3476
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Endotoxin Tolerance in Mouse Peritoneal Macrophages Correlates with Down-Regulation of Surface Toll-Like Receptor 4 Expression

Abstract: Monocytes/macrophages exposed to LPS show reduced responses to second stimulation with LPS, which is termed LPS tolerance. In this study, we investigated molecular mechanism of LPS tolerance in macrophages. Mouse peritoneal macrophages pre-exposed to LPS exhibited reduced production of inflammatory cytokines in a time- and dose-dependent manner. Activation of neither IL-1 receptor-associated kinase nor NF-κB was observed in macrophages that became tolerant by LPS pretreatment, indicating that the proximal even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
519
8
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 694 publications
(593 citation statements)
references
References 30 publications
57
519
8
9
Order By: Relevance
“…However, the degree of LPS tolerance is reportedly dependent on the timing of LPS injection. 14 In separate experiments, the 'challenge' dose of LPS was given 6 h (not 24 h) after the 'inducing' LPS dose at which time tolerance was only detected in p53 − / − animals (Supplementary Figure S7B). Thus, depending on the experimental circumstances, loss of p53 predisposes to the development of LPS tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…However, the degree of LPS tolerance is reportedly dependent on the timing of LPS injection. 14 In separate experiments, the 'challenge' dose of LPS was given 6 h (not 24 h) after the 'inducing' LPS dose at which time tolerance was only detected in p53 − / − animals (Supplementary Figure S7B). Thus, depending on the experimental circumstances, loss of p53 predisposes to the development of LPS tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently RelB inhibitor‐treated autologous DC have shown efficacy in a Phase 1 clinical trial of patients with rheumatoid arthritis 13. Interestingly, although most of the studies investigating ET have been in vitro studies in which macrophages,39, 75 and less so DC,35 are refractory to a second challenge with LPS (“homotolerance”) a few studies have shown that macrophages pre‐exposed to one TLR‐agonist become unresponsive to challenge with another TLR‐agonist (“heterotolerance”). For instance, LPS‐primed macrophages fail to respond to a second challenge with extracts from other Gram‐negative bacteria 37, 64, 76.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we showed that IL-1b at 30-50 ng/ml alone is also capable of inducing a dose-dependent down-regulation of the expression of TLR4 in macrophages in vitro. This is a crucial molecule for LPS signalling which has recently been found to be down-regulated on peritoneal cells from LPS-tolerant mice [21]. Whether the mechanism triggered by IL-1b is similar to LPS is not known, although it had been previously demonstrated that TLR4-mediated signalling induced by LPS is homologous to that of IL-1 signalling [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that Toll-like receptor 4 (TLR4), an essential signalling receptor for LPS, is down-regulated in LPS-tolerant mouse peritoneal macrophages [21]. This downregulation correlates with the impairment of the production of pro-inflammatory cytokines such as TNF-a, IL-6 and IL-12.…”
Section: Il-1b Induces Down-regulation Of Tlr4 On Mouse Peritoneal Mamentioning
confidence: 99%